Interleukin-6 and highly sensitive C-reactive protein in obese adolescents - Michael Kasenda; Suryadi Tantura; Sarah Warouw (Paediatrica Indonesiana, 2012)
Background Childhood obesity is a major health concern.Obesity is due to an expansion of adipose tissue mass. This tissueproduces proô€žinflarmnatory cytokines, such as interleukinô€ž6 (IL--6).ILô€ž6 is considered to be the chief stimulator of the production ofhighly sensitive Cô€žreactive protein (hsCRP) in the liver. Bothmolecules are responsible for the chronic lowô€žgrade inflammatorystate in obese individuals.Objective To assess a correlation between ILô€ž6 and hsCRP inobese adolescents.Methods This crossô€žsectional study was conducted from Marchto June 2011 in Manado. Subjects were obese and normal bodymass index (BMI) teens aged 13ô€ž18 years. Serum glutamicoxaloacetic transaminase (SOOT) and serum glutamic pyruvictransaminase (SOPT) levels were measured to rule out liverimpairment. ILô€ž6 and hsCRP levels were also measured. Data wasanalyzed by Pearson's correlation and linear regression to test forcorrelation between IL--6 and hsCRP levels.Results There was a strongly positive correlation between ILô€ž6and hsCRP levels in obese adolescents (r=0.79 with P<O.OOl).IL--6 and hsCRP levels were not significantly associated in subjectswith normal BMI.Conclusions There was a strongly positive correlation betweenIL--6 and hsCRP levels in obese adolescents, suggestive of anongoing, chronic, lowô€žgrade inflammatory state. [PaediatrIndanes.2012;52:219-22].